2008
DOI: 10.1523/jneurosci.2954-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Survival of Newly Generated Neurons: When Time Matters

Abstract: New interneurons are continually added to the olfactory bulb (OB), the first central relay for processing olfactory information, throughout life. It remains unknown how these adult-generated interneurons integrate into preexisting networks or die. We used immunohistochemical approaches to quantify adult neurogenesis in mice subjected to olfactory training. We identified a critical period in the life of an adult-generated OB interneuron, during which learning triggers distinct consequences. Using a discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
150
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(166 citation statements)
references
References 28 publications
13
150
3
Order By: Relevance
“…In addition, it introduces the pre-integration phase that overlaps with the critical period for maturation of adult-born cells (around 10-25 days after birth), when sensory activity critically impacts on their survival [39,41,42]. Our study has opened new fields of investigation for (i) understanding the mechanisms underlying lateral migration and its implication for adult neurogenesis (ii) applying this new knowledge in developing/testing new strategies in stem cell therapy.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it introduces the pre-integration phase that overlaps with the critical period for maturation of adult-born cells (around 10-25 days after birth), when sensory activity critically impacts on their survival [39,41,42]. Our study has opened new fields of investigation for (i) understanding the mechanisms underlying lateral migration and its implication for adult neurogenesis (ii) applying this new knowledge in developing/testing new strategies in stem cell therapy.…”
Section: Discussionmentioning
confidence: 95%
“…Mechanisms related to altered cell turnover of OSNs may play an important role. Previous work has shown that associative olfactory learning modulates the survival of newborn neurons and increases the survival of adultborn neurons in the OB (29)(30)(31)(32). Although these studies investigated the contribution of olfactory neurogenesis to learning at the level of the OB, learning-dependent regulation of epithelial olfactory neurogenesis, in which OSNs are in direct contact with environmental cues, may play a similarly and perhaps even greater role in shaping sensory epithelial responses to learning.…”
Section: Discussionmentioning
confidence: 99%
“…Correlative studies have suggested a role of neurogenesis in associative discrimination learning (14,22,23), as well as an impairment of spontaneous discrimination due to a low rate of neurogenesis (19,24). However, a recent study reported no effect of blockade of neurogenesis on olfactory discrimination learning (25).…”
Section: Discussionmentioning
confidence: 99%